1998
DOI: 10.1159/000017354
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Proteolipid Protein: Function in Myelin Structure Is Distinct from Its Role in Oligodendrocyte Development

Abstract: The myelin proteolipid proteins PLP and DM20 are essential for the compaction of central nervous system myelin and they play an important role in the maturation of the oligodendrocyte. The specific function of the less abundant DM20 isoform is still unknown, but rescue experiments previously indicated that both isoforms are necessary for oligodendrocyte maturation. In vitro experiments have suggested DM20 may assist in the translocation of PLP into the membrane. We tested this hypothesis in vivo, by investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…In fact, it has been shown that both isoforms, but particularly DM20, are required for oligodendrocyte maturation (Nadon and West, 1998). Our studies, as well as others (Spassky et al, 1998), demonstrate that the plp gene is expressed much earlier in the oligodendrocyte lineage than originally thought (Figs.…”
Section: Plp/dm20 Protein Expression In Neonatal Cortexsupporting
confidence: 69%
“…In fact, it has been shown that both isoforms, but particularly DM20, are required for oligodendrocyte maturation (Nadon and West, 1998). Our studies, as well as others (Spassky et al, 1998), demonstrate that the plp gene is expressed much earlier in the oligodendrocyte lineage than originally thought (Figs.…”
Section: Plp/dm20 Protein Expression In Neonatal Cortexsupporting
confidence: 69%
“…These findings are supported by in vitro transfection experiments indicating that DM20 assists in the translocation of PLP to the cell surface (Timsit et al, 1992a;Sinoway et al, 1994;Gow et al, 1994;Thomson et al, 1997). In the rumpshaker Plp mutant mouse, which expresses significant amounts of DM20 on the oligodendrocyte surface, correction of the abnormal myelin structure was achieved by adding wild-type PLP alone by way of a transgene (Nadon and West, 1998). However, normalizing the myelin structure did not correlate with alleviation of the oligodendrocyte developmental block.…”
mentioning
confidence: 87%
“…5 It is also worth mentioning that DM20 doesn't appear in the same state in the CNS and PNS; in the central nervous system it's part of a membrane, while in the peripheral system it's found in cytoplasm of the cell. 6 In addition, even though PLP and DM20 are major players in stabilizing of myelin sheet, they are actually not essential Fig 1.…”
Section: Composition Of Myelin: Proteinsmentioning
confidence: 99%